Magnetic Properties of fe20 ni80 Antidots: Pore Size and Array Disorder - Escrig-Murua, J; Palma-Solorza, J; Casagrande-Denardin, J (Elsevier B.V., 2013)
Magnetic properties of nanoscale Fe20Ni80 antidot arrays with different hole sizes prepared on top of nanoporous alumina membranes have been studied by means of magnetometry and micromagnetic simulations. The results show a significant increase of the coercivity as well as a reduction of the remanence of the antidot arrays, as compared with their parent continuous film, which depends on the hole size introduced in the Fe20Ni 80 thin film. When the external field is applied parallel to the antidots, the reversal of magnetization is achieved by free-core vortex propagation, whereas when the external field is applied perpendicular to the antidots, the reversal occurs through a process other than the coherent rotation (a maze-like pattern). Besides, in-plane hysteresis loops varying the angle show that the degree of disorder in the sample breaks the expected hexagonal symmetry. © 2013 Elsevier B.V. All rights reserved.